The future is now - Mouzouropoulos, Theseas (My University, 2026)
Poster Presented at the The 4th Emirates International Poster Festival. EIPF selected 100 designers to introduce poster images that reflect the theme of UAE CENTENNIAL 2071 "Be Part of the Future... Design Now! Emirates International Poster Festival (EIPF) is a unique creative platform in the MENA region developed to showcase and celebrate contemporary poster design from around the world. This is an initiative of the Cultural and Scientific Association (NADWA) in Dubai to expand creative expression and to promote graphic design practice and creative thinking in the MENA region. Posters provide an invaluable form of visual communication for sharing information, human thoughts, response to local and global issues, promoting products or services.